IMPLEMENTASI KEBIJAKAN PENGGUNAAN DANA BOS DAN LAPORAN KEUANGAN BOS - Rahmad Hidayat; Agus Suryono (Universitas Tribhuwana Tunggadewi, 2014)
Education is an important factor for a country. Many of the policies issued by the government in this area, one of which policies the School Operational Grant (BOS-Bantuan Operasional Sekolah). This study aims to determine how the implementation of the policy on the use of funds and financial reports BOS at SMPN 3 Woha and SMPN 3 Palibelo . This type of research is descriptive qualitative approach. The results showed, the process of policy implementation and use of funds in the financial reports BOS SMPN 3 Woha and SMPN 3 Palibelo been implemented but not optimal. There are differences in the implementation of the use of the funds in these two schools. As for financial reporting mechanisms, the two schools that SMPN 3 Woha and SMPN 3 Palibelo have followed the existing technical such as the school work plan and budget (RKAS-Rencana Kegiatan dan Anggaran Sekolah), bookkeeping, realization of each source of funds of funds, proof of expenditure, reporting, and time reporting is already available in each school, although not optimal.